AKTUALISASI SIMBOL-SIMBOL PERLAWANAN DALAM PERTUNJUKAN MUSIK HIP-HOP TRAHGALI SOULJA DI SURAKARTA - Surya Purnama Putra (Institut Seni Indonesia Surakarta, 2019)
This paper contains the actualization of resistance symbols contained in the performances of Trahgali Soulja, a hip-hop music group based in Surakarta. This includes reviewing the audience’s response to the music performed. The problems that arise are (1) the efforts of the Soulja Trahgali music group in constructing the symbols of resistance, (2) the form of actualization of ideas or the construction of symbols through the stage actions performed by Trahgali Soulja that illustrate the ideology of resistance, and ( 3) audience’s response to the stage action offered by Trahgali Soulja. The production and packaging of Trahgali Soulja’s performances are carried out on the backstage/back region - including the discovery of musical ideology, the process of interpreting the ideology of resistance, and the behind-the-scene communications among players. Then a scenario for the performance is employed in the stage action on the front stage/front region, and of course there are elements to support the performances being prepared. The positive response is shown by the audience with the emergence of the Red Ax Soldier community which supports the entire behavior of Trahgali Soulja, and not even rarely did this community adopt the musical behavior of Trahgali Soulja. In addition, social media such as Facebook, YouTube and Instagram also become the showrooms for this group’s hip-hop songs.Keywords: actualization, symbol of resistance, hip-hop music performances, trahgali soulja.